Optimalisasi Jadwal Kegiatan Belajar Mengajar di MI NW I Talun Selama Pandemi Covid-19 - Bulqis Nebulla Syechah (Unisda Journal of Mathematics and Computer Science (UJMC), 2021)
The Covid-19 pandemic has impacted many areas of life, including education in Indonesia. After the Indonesian government implemented a lockdown in a few months, now we are in a new normal era where everyone can do any activity based on the covid-19 protocol. In the new normal era, students and teachers are allowed to do teaching and learning activities with an offline system based on the Covid-19 protocol, this makes the schedule ineffective, such as in MI NW 1 Talun. At this school, each class has a schedule to do learning activities three times a week. Based on this, in this study, the authors will offer a schedule formulated based on variables of teachers, students, classes, classrooms, days and times, and covid-19 protocols. This research method is a genetic algorithm that is a method of optimization based on natural selection. The results of this study show that the new schedule is more effective than before and every student or teacher can do teaching and learning activities to the maximum and avoid covid-19.